Evaluation of safety attitudes of hospitals and the effects of demographic factors on safety attitudes: a psychometric validation of the safety attitudes and safety climate questionnaire - Chuang Zhao; Qing Chang; Xi Zhang; Qijun Wu; Nan Wu; Jiao He; Yuhong Zhao (BMC, 2019)
Abstract Background The objectives of this study are to test the psychometric properties of the safety attitudes and safety climate questionnaire Chinese simplified version (SAQ-CS), to test the safety attitudes of health professionals in tertiary hospitals in the Liaoning province and to explore the effects of demographic factors on safety attitudes. Methods The SAQ-CS was used to conduct a cross-sectional survey in nine tertiary hospitals in Liaoning province. Results Cronbach's alpha of each subscale of SAQ-CS were > 0.7, the values of GFI, TLI, and CFI were > 0.8, and RMSEA values ranged from 0.048-0.199. The mean of the safety attitudes of 2157 health professionals was 4.00, indicating a good safety attitude, with a positive response rate (% of items that scored ≥4) of 51.1%. The stress recognition subscale had the lowest score, with a mean of 2.73 and a positive response rate of 17.8%. A multiple linear regression equation revealed that demographic factors like gender, age, and training participation significantly affected the scores (βgender > 0.06, βage < − 0.08, βtraining < − 0.07, p < 0.05). Conclusions The psychometric properties of SAQ-CS are good and stable. Health professionals rate teamwork climate, safety climate, perception of management, and work conditions in Liaoning province are perceived as good; however, the stress of the health professionals is poor. To improve safety attitudes, it is necessary to not only reduce the stress of health professionals, but also to pay more attention to men, older health professionals, and health professionals who have not participated in safety training.